Novel Strategies Enhancing Bioavailability and Therapeutical Potential of Silibinin for Treatment of Liver Disorders - Selc M; Macova R; Babelova A (Dove Medical Press, 2024)
Michal Selc,1,2 Radka Macova,2,3 Andrea Babelova1,2 1Centre for Advanced Material Application, Slovak Academy of Sciences, Bratislava, Slovakia; 2Department of Nanobiology, Cancer Research Institute, Biomedical Research Center, Slovak Academy of Sciences, Bratislava, Slovakia; 3Department of Genetics, Faculty of Natural Sciences, Comenius University Bratislava, Bratislava, SlovakiaCorrespondence: Michal Selc, Centre for Advanced Material Application, Slovak Academy of Sciences, Bratislava, 84511, Slovakia, Tel +421-2-32295-175, Email michal.selc@savba.skAbstract: Silibinin, a bioactive component found in milk thistle extract (Silybum marianum), is known to have significant therapeutic potential in the treatment of various liver diseases. It is considered a key element of silymarin, which is traditionally used to support liver function. The main mechanisms of action of silibinin are attributed to its antioxidant properties protecting liver cells from damage caused by free radicals. Experimental studies conducted in vitro and in vivo have confirmed its ability to inhibit inflammatory and fibrotic processes, as well as promote the regeneration of damaged liver tissue. Therefore, silibinin represents a promising tool for the treatment of liver diseases. Since the silibinin molecule is insoluble in water and has poor bioavailability in vivo, new perspectives on solving this problem are being sought. The two most promising approaches are the water-soluble derivative silibinin-C-2',3-dihydrogen succinate, disodium salt, and the silibinin-phosphatidylcholine complex. Both drugs are currently under evaluation in liver disease clinical trials. Nevertheless, the mechanism underlying silibinin biological activity is still elusive and its more detailed understanding would undoubtedly increase its potential in the development of effective therapeutic strategies against liver diseases. This review is focused on the therapeutic potential of silibinin and its derivates, approaches to increase the bioavailability and the benefits in the treatment of liver diseases that have been achieved so far. The review discusses the relevant in vitro and in vivo studies that investigated the protective effects of silibinin in various forms of liver damage. Keywords: silybin, bioavailability, liver disease, silibinin-phosphatidylcholine complex, silibinin-C-2' 3-dihydrogen succinate